The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1136/jech.45.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Influence of "diagnostic delay" upon cancer survival: an analysis of five tumour sites.

Abstract: Study objective-The aim was to assess the relationship between survival, tumour stage, and the interval from first symptom to diagnosis (SDI, or duration of symptoms).Design-This was a retrospective follow up study ofa cohort ofpatients registered in the tumour registry of the Hospital del Mar (Barcelona).Setting-Hospital based tumour registry, with patients derived mainly from the City of Barcelona.Participants-1247 cases of lung, breast, stomach, colon, or rectal cancer were analysed using survival curves an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 41 publications
(8 reference statements)
1
70
0
2
Order By: Relevance
“…9 A greater delay in diagnosis could be associated with greater mortality in urinary tract, colon and breast cancers, 33,44,45 though other studies have shown no such association for breast, colorectal, lung and gastroesophageal cancers. 26,[44][45][46][47] Still other studies found elevated mortality with short diagnostic intervals for lung cancer 48,49 or high mortality with short and long diagnostic intervals for colorectal cancer (i.e., a salud pública de méxico / vol. 58…”
Section: Time Between Receipt Of Mammography Results and Diagnostic Bmentioning
confidence: 99%
See 1 more Smart Citation
“…9 A greater delay in diagnosis could be associated with greater mortality in urinary tract, colon and breast cancers, 33,44,45 though other studies have shown no such association for breast, colorectal, lung and gastroesophageal cancers. 26,[44][45][46][47] Still other studies found elevated mortality with short diagnostic intervals for lung cancer 48,49 or high mortality with short and long diagnostic intervals for colorectal cancer (i.e., a salud pública de méxico / vol. 58…”
Section: Time Between Receipt Of Mammography Results and Diagnostic Bmentioning
confidence: 99%
“…Variables that had a p<0.20 in the bivariate analysis and those considered by the literature were taken into account in the multiple analysis. 7,9,12,[24][25][26][27][28][29] The life 40.7% in stage III, and 7.4% in stage IV. The median health care times estimated in the study were the following: total time = 139 natural days (IQR=82.5-258), time from when a woman felt a symptom to when she consulted about a doctor about it = 30 natural days (IQR=6-150), time from the receipt of the suspicious mammography results to diagnostic biopsy = 31 natural days (IQR=14-56) and time from diagnostic biopsy to initiation of treatment = 37 natural days (IQR=18-63).…”
Section: Discussionmentioning
confidence: 99%
“…In another study 6 out of 29 patients became clinically incurable while waiting (9). The other studies did not nd any association between advanced stage:survival and delay (6,7,11).…”
Section: The Prognostic Impact Of Delaymentioning
confidence: 97%
“…There is a need for a screening programme to pick up breast cancers early as it has been shown that early diagnosis leads to better survival especially in breast cancer. 5,13,14 Along with this there should be decentralization in the government health infrastructure enabling easy access to surgeons and pathologists so that delay caused by reference to higher centre can be avoided.…”
Section: Discussionmentioning
confidence: 99%